Proteome Analysis of the Soybean Nodule Phosphorus Response Mechanism and Characterization of Stress-Induced Ribosome Structural and Protein Expression Changes - Yao, Yubo; Yuan, Hongmei; Wu, Guangwen; Ma, Chunmei; Gong, Zhenping (Frontiers in Plant Science, 2022)
In agroecosystems, a plant-usable form of nitrogen is mainly generated by legume-based biological nitrogen fixation, a process that requires phosphorus (P) as an essential nutrient. To investigate the physiological mechanism whereby phosphorus influences soybean nodule nitrogen fixation, soybean root nodules were exposed to four phosphate levels: 1 mg/L (P stress), 11 mg/L (P stress), 31 mg/L (Normal P), and 61 mg/L (High P) then proteome analysis of nodules was conducted to identify phosphorus-associated proteome changes. We found that phosphorus stress-induced ribosomal protein structural changes were associated with altered key root nodule protein synthesis profiles. Importantly, up-regulated expression of peroxidase was observed as an important phosphorus stress-induced nitrogen fixation-associated adaptation that supported two nodule-associated activities: scavenging of reactive oxygen species (ROS) and cell wall growth. In addition, phosphorus transporter (PT) and purple acid phosphatase (PAPs) were up-regulated that regulated phosphorus transport and utilization to maintain phosphorus balance and nitrogen fixation function in phosphorus-stressed root nodules.